How felt obligation and organization engagement mediate the relationship between perceived organizational support and work life balance amid COVID-19 pandemic: empirical evidence from emerging countries - Tan L.P. (2023)
Drawing from Organizational support theory (OST), we develop and test a mediation model of felt obligation and Organizational Engagement (OE) between Perceived Organizational Support (POS) and Work Life Balance (WLB). Specifically, we examine the moderating effect of ethnic dissimilarity on the mediating effect of felt obligation between POS and WLB in the context of COVID-19 pandemic with aims to provide nuanced understanding of how the pandemic influences employees’ POS, felt obligation, OE, and WLB to advance OST and extant POS literature. Based on a sample of 467 academics from China and Malaysia. Ethnic dissimilarity is found to be a salient moderator as our results reveal that felt obligation mediates the relationship between POS and WLB in the homogeneous sample but not in the heterogeneous sample through the lens of social exchange. In addition, under the self-enhancement mechanism, our result reveals that OE mediates the relationship between POS and WLB in the samples. Overall, it is envisaged that our findings are timely, and offer valuable theoretical and practical implications for organizations and employees in the COVID-19 pandemic.